Economic growth, income distribution and poverty reduction in contemporary China - Yao, Shujie (RoutledgeCurzon studies on the Chinese economy ;, 2005)
This book reviews the economic development history of contemporary China from 1949 up to today, paying special attention to the interface among growth, inequality and poverty reduction.